bryandustin0708@gmail.com - Briyan Dustin (Fakultas Hukum Universitas Tarumanagara, 2021)
The assault case directed to the senior investigator of The Commission Of Eradication of Corruption, Novel Baswedan is broadly well known and attracted a lot of attention in the media and the attention of most Indonesian. In which the genesis of this case, the continuity and the progress all the way to the capture and arrest of the known preprated individual consume quite for some times, for almost two years, resulting in the majority of the people of Indonesia to looked down upon the investigation of this case and most also considered this as a botched attempt at derailing the truth of the case. This is however, not an idle fact, there are in fact still a lot of parties, who consider the resolution and the verdict of the case as unsatisfying in the eyes of law and the people who keep on watch on the progress of the case, many in fact felt they are being cheated on. Not to mention, especially, the victim himself, Mr Baswedan isn't too fond of the verdict and the decision that the proceeding judge has issued. And therefore, this article was published in hopes of revealing what are the unknown and oftentimes overlooked law facts circulating in this case, and of course to better expand the knowledge and enhanced of some hidden facts in this case to most people, either it s the broader masses, intellectuals, or even the investigator delving into this case themselves.